EFFECT OF TEMPERATURE VARIATION ON LEUTINISING HORMONE, FOLLICLE STIMULATING HORMONE AND CORTISOL HORMONE DURING VARIOUS STAGES OF REPRODUCTION IN CHHOTANAGPURI EWE - VERMA, R.K.; ISHWAR, A.K.; BARMAN, R.S.D.; BHARTI, A. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTThe present study was carried out to see the effect of different housing system on 24non-pregnant healthy Chhotanagpuri ewes which were allocated equally to three differentgroups. Animals of group I were kept between the temperature range of 350C to 400C inintensive system in hot and humid condition, animals of group II were kept under intensivesystem between 200C-270C and animals of group III were kept under extensive system andserved as control. The ewes allotted to different treatment groups were of nearly similar ageand body weight. The physiological considerations like reproductive hormones LH, FSH andother important metabolic hormones like Cortisol plays vital role in regulating thereproductive efficiency. Therefore Plasma LH, plasma FSH and plasma Cortisol hormonesconcentration were estimated during the experimental period. The study revealed that thePlasma LH and plasma FSH concentration between different groups did not vary significantly(p